Aqueous Tuber Extracts of Tylosema fassoglense (Kotschy ex Schweinf.) Torre and Hillc. (Fabaceae). Possess Significant In-Vivo Antidiarrheal Activity and Ex-Vivo Spasmolytic Effect Possibly Mediated by Modulation of Nitrous Oxide System, Voltage-Gated Calcium Channels, and Muscarinic Receptors - Mapesa, Washika Amos; Waweru, Mwangi Peter; Bukachi, Frederick; Wafula, Kayaja David (Frontiers in Pharmacology, 2021)
Tylosema fassoglensis (TFG) is used as an antidiarrheal traditional medicine in Western Kenya. This study aimed to investigate the antidiarrheal activity of its aqueous extracts in-vivo and the putative mechanism (s) of action ex-vivo using Sprague-Dawley rats and New Zealand white rabbits respectively. The in-vivo antidiarrheal effects of the extract were evaluated in castor oil-induced diarrhea, the castor oil-induced enteropooling, and phenol red gastric motility tests. On the other hand, isolated rabbit’s jejunal segments were used to evaluate the spasmolytic effect of TFG on spontaneous contraction, in acetylcholine-induced contraction, in presence of 80mMK+, calcium chloride-induced contraction as well as in presence of the following antagonists: naloxone, methylene blue, L-NAME, prazosin, and propranolol in the ex-vivo studies. The data were express as Mean± S.E.M and analyzed by one-way ANOVA and Tukey’s post hoc test in cases of significance which was set at p<0.05. The extract was phytochemically characterized using Liquid chromatography Mass spectroscopy (LC-MS). The extract possessed significant inhibitory effect in the in-vivo experiments. The extract exhibited significant spasmolytic effect on both spontaneous contraction and in jejunal segment pre-contracted acetylcholine as well as in presence of 80mMK+ solution. It also attenuated the spasmogenic effect of various concentration of calcium chloride. The extract’s spasmolytic effect was, however, significantly attenuated in presence of several antagonists (methylene blue and L-NAME) but the adrenergic blockers (prazosin and propranolol) had no significant effect in the ex-vivo studies. LC-MS identified thirty compounds where Proathocyanidin (11.54%), Syringic acid (7.30%), and 4-Hydroxybenzoic acid (6.19%) had the highest percentage abundance. In conclusion, the results obtained in this study partially validate the traditional uses of the tubers of this plant species as an antidiarrheal. These antidiarrheal effects are probably mediated via modulation of nitrous oxide pathway, voltage gated calcium channels, and muscarinic receptors.